2011
DOI: 10.1073/pnas.1107202108
|View full text |Cite
|
Sign up to set email alerts
|

Ancient lipids reveal continuity in culinary practices across the transition to agriculture in Northern Europe

Abstract: Farming transformed societies globally. Yet, despite more than a century of research, there is little consensus on the speed or completeness of this fundamental change and, consequently, on its principal drivers. For Northern Europe, the debate has often centered on the rich archaeological record of the Western Baltic, but even here it is unclear how quickly or completely people abandoned wild terrestrial and marine resources after the introduction of domesticated plants and animals at ∼4000 calibrated years B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
197
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(218 citation statements)
references
References 28 publications
11
197
1
9
Order By: Relevance
“…Although this approach has been widely applied to study the use of East Asian pottery (19,20), it offers only crude resolution of contents because of uncertainties in the isotope end-points of different foodstuffs and because of diagenetic alteration (21). The δ 15 N values of 75% of charred deposits analyzed ranged between 8.8‰ and 13.4‰ ( range has been previously observed in charred ceramic deposits from different coastal archaeological sites associated with the exploitation of fish and marine mammals (22,23), and is more consistent with reference tissues from aquatic organisms than terrestrial animals or plants (24), although mixing of the latter cannot be ruled out or accurately quantified using this approach. We note, however, that over 90% of the samples have atomic C:N ratios less than 12 (median = 9.7) (Table S1), which characterize protein rich foods rather than starchy plants (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this approach has been widely applied to study the use of East Asian pottery (19,20), it offers only crude resolution of contents because of uncertainties in the isotope end-points of different foodstuffs and because of diagenetic alteration (21). The δ 15 N values of 75% of charred deposits analyzed ranged between 8.8‰ and 13.4‰ ( range has been previously observed in charred ceramic deposits from different coastal archaeological sites associated with the exploitation of fish and marine mammals (22,23), and is more consistent with reference tissues from aquatic organisms than terrestrial animals or plants (24), although mixing of the latter cannot be ruled out or accurately quantified using this approach. We note, however, that over 90% of the samples have atomic C:N ratios less than 12 (median = 9.7) (Table S1), which characterize protein rich foods rather than starchy plants (20).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly high δ 15 N values have been found in charred deposits on Jōmon pots throughout the Japanese archipelago (9,19,20). Lipid residue analysis has shown that marine and freshwater products were frequently processed in pottery produced by Holocene hunter-gatherers from Northeastern North America (22) and the Baltic (23,41), and in Japan as late as the Final Jōmon phase (1000-400 B.C.) (42).…”
Section: Discussionmentioning
confidence: 99%
“…Significant amount of unsaturated FAs (C16:1, C18:1, and C18:2) were also detected, with octadecenoic (C18:1) acids present in high abundance. Isoprenoid FAs (4,8,12-TMTD, pristanic acid, and phytanic acid) and other FAs [long-chain ω-(o-alkylphenyl) alkanoic acids, and dihydroxy FAs] used as marine biomarkers (3)(4)(5)(6)(7)(8)43) were absent from the USR hearths. The δ 13 C 16:0 and δ 13 C 18:0 values from the USR hearths were measured to discriminate between marine and freshwater food groups, which could not be achieved using δ 15 N values alone.…”
Section: Resultsmentioning
confidence: 99%
“…stable isotopes | hearths | organic residue analysis | GC-combustion-IRMS | Beringia I nferences on ancient hunter-gatherer subsistence economies generally rely on zooarchaeologically derived abundance measures from sites with faunal preservation (1); however, these sites can be rare in late-Pleistocene deposits (2). Chemical profiling using compound-specific stable isotope analyses can provide another approach to reconstruct resource use and have been used to study food residues on pottery (3)(4)(5)(6)(7)(8). These isotopic studies have provided insights into the proportional contributions of different food resources to human diets, particularly aquatic vs. terrestrial food sources.…”
mentioning
confidence: 99%
“…Interestingly, light pigmentation-associated alleles in different genes are common in Asian populations who also have light skin color, indicating that light skin pigmentation has evolved multiple times independently. Both the high haplotype homozygosity and its restricted geographic range suggest that the selective sweep on SLC24A5 occurred recently, perhaps during the Holocene with the shift from a vitamin D-rich (fish) hunter-gatherer diet to a vitamin D-poor farming diet (but see Craig et al 2011).…”
Section: Genome-wide Variation and Natural Selection In European Popumentioning
confidence: 99%